The Birefringence and Extinction Coefficient of Ferroelectric Liquid Crystals in the Terahertz Range - Ying Ma; Yuhang Shan; Yongning Cheng; Ruisheng Yang; Hoi-Sing Kwok; Jianlin Zhao (Photonics, 2023)
In this paper, the refractive index and extinction coefficient of ferroelectric liquid crystals have been examined by the terahertz time-domain spectroscopy system. Two modes of ferroelectric liquid crystal materials, deformed helix ferroelectric liquid crystal (DHFLC), and electric suppressed helix ferroelectric liquid crystal (ESHFLC) are tested as experimental samples. Nematic liquid crystal (NLC) was also investigated for comparison. The birefringence of DHFLC 587 slowly increases with the growth of frequency, and it averages at 0.115. Its extinction coefficients gradually incline to their stable states at 0.06 for o-wave and 0.04 for e-wave. The birefringence of ESHFLC FD4004N remains between around 0.165 and 0.175, and both of its e-wave and o-wave extinction coefficients are under 0.1, ranging from 0.05 to 0.09. These results of FLC will facilitate the examination and improve the response performance of THz devices using fast liquid crystal materials.